2015
DOI: 10.1016/j.sbspro.2015.02.395
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Sample Lesson Plan for Secondary Science Courses within the STEM Education

Abstract: The main goal of this study is to present a sample lesson plan on acids and bases based on Science, Technology, Engineering and Mathematic (STEM) education for Turkish Science Education System. Determining the impact of instructional materials on learning outcomes of children as a pilot study before the main implementation is also another goal. Single group pre-test/post-test design was used in the study. 12 different 8 th grade students were chosen for the population of the study. The instructional materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
15

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 0 publications
1
25
0
15
Order By: Relevance
“…STEM applications indicated that that treatments based on STEM applications and mastery learning had positive effect on students' increasing academic achievement. This result is also supported by the results of studies which show that STEM applications have positive effect in increasing academic achievements of students (Ceylan and Özdilek, 2015;Cotabish, Dailey, Robinson and Hunghes, 2013).…”
Section: Discussionsupporting
confidence: 64%
“…STEM applications indicated that that treatments based on STEM applications and mastery learning had positive effect on students' increasing academic achievement. This result is also supported by the results of studies which show that STEM applications have positive effect in increasing academic achievements of students (Ceylan and Özdilek, 2015;Cotabish, Dailey, Robinson and Hunghes, 2013).…”
Section: Discussionsupporting
confidence: 64%
“…This might be due to the fact that only the description of the STEM set is taken into consideration at the workshop. Generally four disciplines of STEM education combined to teach a science subject were used in the studies [8]. It is needed new studies about the combination of disciplines to teach other disciplines except for science.…”
Section: Discussionmentioning
confidence: 99%
“…Bu sonuç Karaçalli ve Korur (2014) ;Lou, Tsai, Tseng ve Shih (2014) ;Rabitoy, Hoffman ve Person'ın (2015) ve Robinson, Dailey, Hughes ve Cotabish (2014) yaptıkları çalışmalarda, STEM-PJT'nin öğrencilerin akademik başarısını arttırdığı sonucu ile örtüşmektedir. Çalışmada, eğitimde kullanılan yeni bir trend olan STEM-PJT uygulamasının, alanyazında STEM-PJT'nin akademik başarıyı arttırdığı sonucu ile paralellik gösteren birçok çalışmayla karşılaşmak mümkündür (Bennett, Lubben & Hogarth, 2007;Bybee, 2010;Ceylan, 2014;Ceylan & Özdilek, 2015;Irkıçatal, 2016;Means, Wang, Young, Peters & Lynch, 2016;Yamak, Bulut & Dündar, 2014;Yıldırım & Altun, 2015). Bu çalışmayı özgün kılan ve en önemli kısım olan husus, meslek lisesi öğrencilerine yönelik STEM-PJT çalışması alanyazında Chang vd.…”
Section: Tartışma Sonuç Ve öNerilerunclassified